PENGARUH KUALITAS TATA KELOLA PERUSAHAAN DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA PERUSAHAAN MANUFAKTUR - DAVID DAVID; FRESTIN CHRISNANTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The objective of this research is to obtain emprical evidence about the institutional ownership,managerial ownership,frequency of board of commissioners meetings, frequency of audit committee meetings, firm size, leverage, audit quality, profitability and firm age to earnings management. The population of this research are manufacturing companies that listed in the Indonesia Stock Exchange (IDX) during the period of 2017 to 2019. The sample used in this study are 43 companies selected using purposive sampling method. The hypotheses in this research were tested and analyzed using multiple linear regression analysis with IBM SPSS (Statistical Product and Service Solutions) application tool. The results of this research indicate that the variable profitability has an influence on earnings management, while the variables of institutional ownership, managerial ownership, frequency of board of commissioners meetings, frequency of audit committee meetings, firm size, leverage, audit quality, and firm age have no influence on earnings management